CRC handbook series in nutrition and food - Rechcigl, Miloslav (CRC Press, 1978)
Handbook of Dairy Foods and Nutrition compiles the most current information on the role of dairy foods in a healthy diet. This volume scientifically reviews the full range of fact and fiction concerning the dietary contributions of dairy foods